2016
DOI: 10.20867/thm.22.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of managers' demographic characteristics on CSR practices in the restaurant industry: the case of Slovenia

Abstract: Purpose -The objective of this study is to investigate how restaurant managers' demographic characteristics influence Corporate Social Responsibility (CSR) practices in the restaurant industry. Design/Methodology/Approach -In order to analyze the influence of managers' demographic characteristics on CSR practices, industry specific practices relevant to the Slovenian restaurant industry were identified: regular financial assistance to activities and projects of the local community, employment of local staff, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 78 publications
0
12
0
4
Order By: Relevance
“…In addition to these recommendations, it is necessary to strengthen the research of halal tourism in Slovenia, since this would help to overcome stereotypes and strengthen the awareness of hotel managers and other relevant stakeholders in tourism about the potentials/opportunities, to connect the specific business concept with the specific sectarian organisational culture 10 and provide a level of quality that is consistent with the expectations of the guests (see Parasuraman, Zeithaml & Berry (1985) or Kukanja, Gomezelj Omerzel & Kodrič (2016)). In this sense, this research could help develop national halal systems in Slovenia and in the wider region as well as improve the perception of hotel managers and facilitating an easier integration of services adjusted to the needs of Muslims (as well as other guests) in the hotel facilities and services; the perspective of corporate social responsibility (CSR) in the hospitality industry should not be neglected (see Kukanja, Planinc & Šuligoj (2016) or Štrukelj & Šuligoj (2014)). …”
Section: Discussionmentioning
confidence: 99%
“…In addition to these recommendations, it is necessary to strengthen the research of halal tourism in Slovenia, since this would help to overcome stereotypes and strengthen the awareness of hotel managers and other relevant stakeholders in tourism about the potentials/opportunities, to connect the specific business concept with the specific sectarian organisational culture 10 and provide a level of quality that is consistent with the expectations of the guests (see Parasuraman, Zeithaml & Berry (1985) or Kukanja, Gomezelj Omerzel & Kodrič (2016)). In this sense, this research could help develop national halal systems in Slovenia and in the wider region as well as improve the perception of hotel managers and facilitating an easier integration of services adjusted to the needs of Muslims (as well as other guests) in the hotel facilities and services; the perspective of corporate social responsibility (CSR) in the hospitality industry should not be neglected (see Kukanja, Planinc & Šuligoj (2016) or Štrukelj & Šuligoj (2014)). …”
Section: Discussionmentioning
confidence: 99%
“…Golob and Podnar (2014) started from these premises in their research but found that the CSR practices are slightly different in Slovenia, even if there is a strong trade union movement that should be involved in increasing the working conditions of employees and implicitly in social activities, so unions should be more visible in relation to CSR. Kukanja et al (2016) investigated social responsibility practices in the restaurants industry, significant economic area in Slovenia, and the factors that influence them. In study managers' demographics were taken into account and the results were based on responses to direct interviews with 200 restaurant managers in the early part of 2015.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, the issue of CSR in tourism SMEs has received considerable critical attention in scientific literature. A considerable amount of literature has grown up around the theme of explaining the relationship between CSR and SMEs' financial performance (Garriga and Melé, 2004;Kang et al, 2010, Kukanja et al, 2016. According to Kang et al (2010) in most studies research results determined a positive relationship between CSR activities and companies' financial performance.…”
Section: Csr Practices In Tourism Smesmentioning
confidence: 99%
“…Recently, a considerable body of literature has grown up around the theme of CSR measurement. The literature has reviewed CSR practices extensively for the large manufacturing companies (Juščius and Snieška, 2015;KPMG, 2017;Rahman and Post, 2012), yet there is less evidence from the service sector (Kang, Lee and Huh, 2010;Tsai, Tsang and Cheng, 2012) and even less for tourism SMEs (Garay and Font, 2012;Kukanja, Planinc and Šuligoj, 2016).Previous studiesprimarily focused to developed economies, whilst there is a lack of empirical findings for tourism SMEs in post-transitional economies (Renko and Peštek, 2017).…”
Section: Introductionmentioning
confidence: 99%